1988
DOI: 10.1093/ptj/68.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helium-Neon Laser Irradiation on Peripheral Sensory Nerve Latency

Abstract: The purpose of this randomized, double-blind study was to determine the effect of a helium-neon (He-Ne) laser on latency of peripheral sensory nerve. Forty healthy subjects with no history of right upper extremity pathological conditions were assigned to either a Laser or a Placebo Group. Six 1-cm2 blocks along a 12-cm segment of the subjects' right superficial radial nerve received 20-second applications of either the He-Ne laser or a placebo. We assessed differences between pretest and posttest latencies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
1
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 8 publications
(12 reference statements)
5
53
1
5
Order By: Relevance
“…Another mechanism of the pain weakening can be reduction of the conduction velocity in sensory nerves [29][30][31][32][33]. There are evidences that laser irradiation applied to undamaged skin may produce a direct, local effect on conduction in underlying nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism of the pain weakening can be reduction of the conduction velocity in sensory nerves [29][30][31][32][33]. There are evidences that laser irradiation applied to undamaged skin may produce a direct, local effect on conduction in underlying nerves.…”
Section: Discussionmentioning
confidence: 99%
“…This may be an increase in the synthesis and release of endorphins, as well as a decrease in the release of bradykinin and serotonin in the area of inflammation [44,45]. Another mechanism of easing pain is associated with a decrease in the rate of pain signals in sensory nerves [6,[47][48][49][50][51]. In addition, it has been shown that laser light (especially red) increases blood flow, which is accompanied by an improvement in oxygenation and metabolism, with simultaneous enhancement of lymphatic drainage and weakening of edema in the affected tissue, which also contributes to the relief of pain [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Laser application on the distal sensory branch of the radial nerve led to increased latency and decrease velocity. 15 Application on the median nerve in 51 normal volunteers, led to a slight increased latency in sensory antidromic conducting study. 16 Such data were not confirmed by others, whose normal volunteers showed no changes in conduction studies after application of Laser.…”
Section: Introductionmentioning
confidence: 99%